2001
DOI: 10.1063/1.1364654
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous low-voltage tunneling current characteristics of ultrathin gate oxide (∼2 nm) after high-field stress

Abstract: The effect of oxide barrier shape change caused by stress-induced interface trap charges on the low-voltage tunneling current ͑LVTC͒ characteristics of ultrathin gate oxide ͑ϳ2 nm͒ is studied in this work. It was found that for an ultrathin gate oxide working in the direct tunneling regime, the LVTC behavior is strongly dependent on the barrier shape of the oxide. After high-field stress, anomalous LVTC phenomenon is observed. There is an invariant point existing in current-voltage curves. For a bias smaller t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For other applications the final destructive breakdown event is the important one. In ultra-small devices with ultra-thin oxides, where the stored energy in the capacitor, 1/2 CV 2 may be too low to trigger thermal breakdown, direct tunneling currents, SILCs, and the accompanied power dissipation is probably the most important criteria defining oxide and IC reliability [96,98,237,291,392,[794][795][796][797][798][799][800][801][802]. Dynamic random access memories need a fixed amount of charge stored, and, as the storage area decreases, this requirement leads to the need for high dielectric constant materials or complicated schemes for producing larger area devices while keeping the surface area minimal.…”
Section: Reliabilitymentioning
confidence: 99%
“…For other applications the final destructive breakdown event is the important one. In ultra-small devices with ultra-thin oxides, where the stored energy in the capacitor, 1/2 CV 2 may be too low to trigger thermal breakdown, direct tunneling currents, SILCs, and the accompanied power dissipation is probably the most important criteria defining oxide and IC reliability [96,98,237,291,392,[794][795][796][797][798][799][800][801][802]. Dynamic random access memories need a fixed amount of charge stored, and, as the storage area decreases, this requirement leads to the need for high dielectric constant materials or complicated schemes for producing larger area devices while keeping the surface area minimal.…”
Section: Reliabilitymentioning
confidence: 99%
“…For other applications the final destructive breakdown event is the important one. In ultra-small devices with ultra-thin oxides, where the stored energy in the capacitor, 1/2 CV 2 may be too low to trigger thermal breakdown, direct tunneling currents, SILCs, and the accompanied power dissipation is probably the most important criteria defining oxide and IC reliability [96,98,237,291,392,[794][795][796][797][798][799][800][801][802]. Dynamic random access memories need a fixed amount of charge stored, and, as the storage area decreases, this requirement leads to the need for high dielectric constant materials or complicated schemes for producing larger area devices while keeping the surface area minimal.…”
Section: Reliabilitymentioning
confidence: 99%
“…In ultra-thin oxides, a gate leakage current is measured in depletion regime. This leakage current increases with stress and is referred to as LVSILC (low voltage stress induced leakage current) [1][2][3][4][5][6][7]. In previous papers [3,7], it has been shown that the LVSILC normalized variation presents two degradation peaks.…”
Section: Introductionmentioning
confidence: 99%
“…According to [1], the gate current measured in depletion regime before and after stress [2] is due to a conduction mechanism through interface states. It is then interesting to compare the interface state density variation with the LVSILC one.…”
Section: Introductionmentioning
confidence: 99%